2016
DOI: 10.1016/j.minpro.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance monitoring of a hydrocyclone based on underflow discharge angle

Abstract: The performance of a hydrocyclone as a separation device is never perfect and rigorous research efforts are still continuing along various directions towards achieving optimum solutions. The modus operandi of performance optimization is important for quick and non-invasive monitoring of hydrocyclone performance. Therefore, in the present study, an application potential of spray angle as a performance monitoring tool has been explored to investigate the operation state of a hydrocyclone. In this context, phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…On the other hand, more water going to underflow. This result agrees with the results obtained by other investigators (Ahmed et al, 2009;Dubey et al, 2016;Dueck et al, 2014).…”
Section: Effect Of Underflow Diameter (V ] )supporting
confidence: 94%
“…On the other hand, more water going to underflow. This result agrees with the results obtained by other investigators (Ahmed et al, 2009;Dubey et al, 2016;Dueck et al, 2014).…”
Section: Effect Of Underflow Diameter (V ] )supporting
confidence: 94%
“…The hydrocyclone (Fig. 6) consists of: a cylindrical part (1), giving the mixture a swirl motion; a conical part (2), where a separation occurs due to different grain sizes; an inlet nozzle (3), introducing the mixture, an overflow nozzle (4), receiving fine grains and an outflow nozzle (5), collecting coarse grains [5,8,18,24].…”
Section: Fig 5 Model Of Hydrocyclonementioning
confidence: 99%
“…Pérez et al [14] researched that the discharge angle of a hydrocyclone was an effective indicator to monitor the separation process, coarse feeding, and high-flow velocity conditions triggered the phenomenon of rope discharge in underflow, which reduced the separation accuracy and was accompanied by low-frequency vibration. Dubey et al [15] combined high-speed photography and numerical simulation to quantify the relationship between the discharge angle and each structural parameter. Su et al [16] reported that the design of a thick-walled, smalldiameter vortex finder promoted the suppression of short-circuit flow, reduced coarse particle enrichment within overflow, and minimized the separation cut size.…”
Section: Introductionmentioning
confidence: 99%